2011
DOI: 10.4310/jdg/1320067650
|View full text |Cite
|
Sign up to set email alerts
|

Seiberg-Witten Equations, End-Periodic Dirac Operators, and a Lift of Rohlin's Invariant

Abstract: Abstract. We introduce a gauge-theoretic integer valued lift of the Rohlin invariant of a smooth 4-manifold X with the homology of S 1 × S 3 . The invariant has two terms; one is a count of solutions to the Seiberg-Witten equations on X, and the other is essentially the index of the Dirac operator on a non-compact manifold with end modeled on the infinite cyclic cover of X. Each term is metric (and perturbation) dependent, and we show that these dependencies cancel as the metric and perturbation vary in a gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
120
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(121 citation statements)
references
References 47 publications
(97 reference statements)
1
120
0
Order By: Relevance
“…Similar moduli spaces and Casson-type invariants have been defined by Ruberman and Saveliev [25] for Z[Z]-homology Hopf surfaces, going back to work of Furuta and Ohta [16], and for Z[Z]-homology 4-tori [24]. The first of these is also related in a non-trivial way to Seiberg-Witten theory [21] by work of Mrowka, Ruberman and Saveliev. In particular, these invariants are in general non-vanishing.…”
Section: Introductionmentioning
confidence: 61%
See 2 more Smart Citations
“…Similar moduli spaces and Casson-type invariants have been defined by Ruberman and Saveliev [25] for Z[Z]-homology Hopf surfaces, going back to work of Furuta and Ohta [16], and for Z[Z]-homology 4-tori [24]. The first of these is also related in a non-trivial way to Seiberg-Witten theory [21] by work of Mrowka, Ruberman and Saveliev. In particular, these invariants are in general non-vanishing.…”
Section: Introductionmentioning
confidence: 61%
“…Furthermore, the holonomy sections Hol qi (A) on B i continue to span gl(E) in a neighbourhood of x, because l was chosen so that we have a Sobolev inclusion L 2 l → C 0 , and so the holonmy sections are continuous. Multiplying the finite number of holonomy sections Hol qi (A) with convenient one-forms β i ∈ Ω 1 (B i ; C) supported in small enough neighbourhoods of x, we obtain a perturbation β = (β i ) ∈ V , where all but these finite number of one-forms are zero, so that equation (21) implies that Σ is zero in a neighbourhood U of x. As we also have D − A,α Σ = 0, the unique continuation principle [1] for solutions to the perturbed Dirac equation implies that Σ = 0 on the whole of X.…”
Section: Transversality In the Main Stratummentioning
confidence: 99%
See 1 more Smart Citation
“…• the 4-dimensional Casson-type invariant λ SW (X), defined by Mrowka-Ruberman-Saveliev [10]; • the Frøyshov invariant h(Y, s), defined by Frøyshov [2], where s is the unique spin structure on Y that can be extended to a spin structure on X. (It was proved in [2] that this invariant does not depend on the choice of Y .…”
Section: Introductionmentioning
confidence: 99%
“…(We call Y a cross-section of X.) This invariant has interpretations in terms of Seiberg-Witten theory [21] and conjecturally in terms of Yang-Mills theory [34,35,37,36]. More recently, Frøyshov [5] observed that if X has a cross-section Y that is a rational homology 3-sphere, the invariant h(Y, s X ) ∈ Q associated to the unique Spin c structure s X on Y induced from X, which is defined using monopole Floer homology, is also a smooth invariant of X. Frøyshov's argument uses only the rational homology cobordism invariance property of h(Y, s X ), so it applies verbatim to the version of h(Y, s X ) defined by Kronheimer and Mrowka [14, §39.1] (presumed, but not known, to be equal to Frøyshov's) and the similarly defined Heegaard Floer correction term d(Y, s X ) [25].…”
Section: Introductionmentioning
confidence: 99%